Cryptococcoma in Idiopathic CD4 Lymphopenia. (3rd June 2015) - Alshimemeri, S; Walker, G; Mezei, M; Warner, S; Viana, L; Barton, JJ
Abstract : Idiopathic CD4 lymphopenia is a rare immune disorder that renders patients vulnerable to unusual infections. A 25-year-old female had been diagnosed with idiopathic CD4 lymphopenia (CD4 count of 50/uL) at age 14 after pulmonary infection with atypical mycobacterium, but had since been asymptomatic on Trimethoprim/Sulfamethoxazole prophylaxis. She presented now with 5 weeks of headache, vomiting, diplopia, and vertigo. This had been diagnosed as benign positional vertigo. However, neuro-ophthalmologic exam revealed gaze-evoked nystagmus, impaired smooth pursuit, a left hypertropic skew deviation, left sensorineural hearing loss, gait ataxia and left limb dysmetria. MRI brain showed a 15 mm extra-axial enhancing mass at the left cerebellopontine angle, and chest CT showed pulmonary lesions. CSF Cryptococcal antigen was highly positive (> 1:1024) and CSF culture grew Cryptococcus neoformans variety grubii. She was treated with amphotericin B 175 mg daily and 5-Flucytosine 1000 mg QID for 4 weeks, followed by Fluconazole 400 mg daily, and made an excellent recovery. Cryptococcal infection usually presents as a meningitis, but can occasionally present as a mass lesion. Cryptococcal infection is one of the most common complications in idiopathic CD4 lymphopenia. This case illustrates the importance of neurologic signs in correctly localizing the lesion and the need for high suspicion of serious pathology in patients with rare immune disorders.